2010
DOI: 10.1097/nen.0b013e3181c84a9a
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of a Novel Human In Vitro Blood-Nerve Barrier Model Using Primary Endoneurial Endothelial Cells

Abstract: There are phenotypic and functional differences between vascular endothelium from different tissues and between microvascular and macrovascular endothelial cells (ECs) from the same tissue. Relatively little is known about the human blood-nerve barrier (BNB). We report the development of an in vitro BNB model using primary human endoneurial ECs freshly isolated and purified from decedent sciatic nerves via endoneurial stripping, connective tissue enzymatic digestion, and density centrifugation. Primary human e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
153
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(160 citation statements)
references
References 70 publications
6
153
0
1
Order By: Relevance
“…These molecules compose TJs and limit the paracellular permeability in order to maintain the brain microenvironment. Previous reports have indicated that PnMECs in human sural nerves express occludin, claudin-5 and ZO-1 (Kanda et al, 2004), and claudin-1 was detected in perineurium (Hirakawa et al, 2003), primary human PnMECs (Yosef et al, 2010) and human Schwann cells (Alanne et al, 2009). We also reported that rat PnMECs expressed many molecules forming tight junctions (Sano et al, 2007).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…These molecules compose TJs and limit the paracellular permeability in order to maintain the brain microenvironment. Previous reports have indicated that PnMECs in human sural nerves express occludin, claudin-5 and ZO-1 (Kanda et al, 2004), and claudin-1 was detected in perineurium (Hirakawa et al, 2003), primary human PnMECs (Yosef et al, 2010) and human Schwann cells (Alanne et al, 2009). We also reported that rat PnMECs expressed many molecules forming tight junctions (Sano et al, 2007).…”
Section: Discussionmentioning
confidence: 64%
“…Another considerable point is the problem of purity of the cells. Yosef et al reported that primary human PnMECs have higher TEER values than FH-BNBs (Yosef et al, 2010). However, these primary cells inevitably contained a small amount of pericytes, which have been reported to promote barrier integrity of the barrier-derived endothelial cells .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two cell types are common within the endoneurial compartment of peripheral nerves, specialized vascular endothelial cells, and Schwann cells necessary for myelination of axons. Claudin 5 is a marker for the specialized endoneurial endothelial cells [41,47]. Therefore, tissues were costained for osterix and claudin 5 ( Fig.…”
Section: Osteoblast Formation Begins In Nervesmentioning
confidence: 99%
“…An important protein, claudin 5, has been shown to be an essential component of restrictive microvascular barriers [3]. This protein is expressed at sites of cell-to-cell contact on human endoneurial endothelial cells in vitro [47]. Mice lacking expression of claudin 5 lack a functional blood-brain barrier (BBB) and die immediately after birth [24].…”
Section: Introductionmentioning
confidence: 99%